2016
DOI: 10.1002/ijc.30075
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression of Y‐box binding protein‐1 is associated with poor prognosis in patients with pancreatic cancer and its knockdown inhibits tumor growth and metastasis in mice tumor models

Abstract: The objective of this study was to examine the implication of Y-box-binding protein-1 (YB-1) for the aggressive phenotypes, prognosis and therapeutic target in pancreatic ductal adenocarcinoma (PDAC). YB-1 expression in PDAC, pancreatic intraepithelial neoplasia (PanIN) and normal pancreas specimens was evaluated by immunohistochemistry, and its correlation with clinicopathological features was assessed in patients with PDAC. The effects of YB-1 on proliferation, invasion and expressions of cell cycle-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
2
14
0
1
Order By: Relevance
“…Y‐box binding protein‐1 (YBX1), encoded by the YBX1 gene, is a member of the cold‐shock protein superfamily and participates in a wide variety of cellular processes . Many studies have indicated that YBX1 expression is significantly elevated and correlates with poor outcome and recurrence in common tumor types, such as pancreatic cancer and melanoma . In addition, YBX1 regulates tumor cell proliferation, apoptosis, invasion, migration and chemoresistance through the related pathways .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y‐box binding protein‐1 (YBX1), encoded by the YBX1 gene, is a member of the cold‐shock protein superfamily and participates in a wide variety of cellular processes . Many studies have indicated that YBX1 expression is significantly elevated and correlates with poor outcome and recurrence in common tumor types, such as pancreatic cancer and melanoma . In addition, YBX1 regulates tumor cell proliferation, apoptosis, invasion, migration and chemoresistance through the related pathways .…”
Section: Introductionmentioning
confidence: 99%
“…7 Many studies have indicated that YBX1 expression is significantly elevated and correlates with poor outcome and recurrence in common tumor types, such as pancreatic cancer and melanoma. 8,9 In addition, YBX1 regulates tumor cell proliferation, apoptosis, invasion, migration and chemoresistance through the related pathways. 10 Multiple key molecules that interact with YBX1 have been shown to be overexpressed in chordoma and contribute to chordoma development, such as hypoxia inducible factor 1 alpha subunit (HIF-1α), a mechanistic target of rapamycin kinase (mTOR) and RB transcriptional corepressor 1 (RB).…”
mentioning
confidence: 99%
“…Высокая экспрессия этого гена ассо-циирована с ухудшением показателя безрецидивной выживаемости больных РМЖ [12], а также больных с другими новообразованиями [13,14]. Кроме того, белок YB-1 является потенциальной мишенью для тар-гетной терапии [15].…”
Section: обзорные статьиunclassified
“…Y-box binding protein-1 (YB-1), originally identified as a member of the cold-shock protein superfamily,7, 8 is overexpressed not only in cancer cells,9, 10, 11, 12 but also in vascular endothelia in tumor tissues 13 . YB-1 plays an important role in proliferation, invasion, multi-drug resistance, and malignant transformation in a variety of cancers 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%